Analisa Perancangan dan Implementasi Pemesanan Secara Online Berbasis Costumer Relationship Management (CRM) - Aggy Pramana Gusman (Universitas Putra Indonesia YPTK Padang, 2019)
The development of internet technology and the ease of access of various communication equipment, have an influence on the style of consumers to shop effectively and efficiently. Web-based electronic commerce in business competition requires more creative and innovative ways to better indulge consumers to remain loyal. Therefore the Costomer Relationship Management (CRM) method is determined by the company to get as many costomers as possible in order to establish good relationships with consumers. Istana Karpet dan Perabot is one of the companies engaged in the sale of furniture. In the process of ordering as long as this happens it is done by the way consumers come directly to the store. The system that has been used often creates obstacles in the process of providing information about the latest products and making orders. In overcoming this problem, the Istana Karpet dan Perabot requires a computational system that is able to introduce its products and place orders online.